Letter - Bragg, E.
1939-02-23 038-0101-002 1 Wetherell Terrace Kilpenhill Dewsbury. 23/2/39 Dear Sir Just a few lines to know if you can help me I want to know if your committee as an orphan little girl I could adopt age about 8 Bright & healthy with no Consumption or Mental or other heditery disease & I prefer one not wearing glasses) I have had a bereavement & lost Mother & my Father died when I was 7 years old I have no sisters or brothers & I was Mother's inseparable companion now I find life very lonely as I am left alone I am 40 years of age lives in my own house & I have a good & modern home I am healthy & strong & good charactor & my income comes from investments. I love children & I could give one every comfort [An] answer will oblige I am Yours Respectfully Miss E. Bragg P.S. I would like a Protestant as I am Church of England Religion 292/946/38/101(II)